Bagus ANALISIS PERSEBARAN RUANG TERBUKA HIJAU MENGGUNAKAN GOOGLE EARTH PRO DI KECAMATAN BULELENG, KABUPATEN BULELENG - Wirya Arta, Putu Arya; Putra, I Wayan Krisna Eka; Yudiwisnawa, I Gede (Jurnal ENMAP (Environment and Mapping), 2024)
Along with the increase in population density and socio-economic activities in an urban area, there is a decrease in the availability of land and the sustainability of green spaces. This research aims to map the distribution of Green Open Space (RTH) in Buleleng Sub-district. This research uses descriptive analysis method by interpreting Satellite Image with On Screen Digitization method using Google Earth Pro software in secondary data acquisition and conducting Ground Check in primary data acquisition. As for the results of this study, based on the results of visual interpretation of satellite images using Google Earth Pro software, in the Green Open Space of Buleleng Sub-district, Agricultural Green Area dominates with an area of 2756.21 Ha from the total area of Green Open Space in Buleleng Sub-district of 2871.94 Ha. The distribution of this Green Open Space has been spread evenly in each village and sub-district within Buleleng Sub-district.